Examining the Plastic Surgery Treatments Applied to Upper Extremities of Kahramanmaraş Earthquake Victims with Crush Injury - Mehmet Fatih Akkoç; Mehmet Ozdemir; Volkan Özel (Turkish Journal of Plastic Surgery, 2025)
Aim: This study aims to examine earthquake-related upper extremity orthopedic injuries, and in our clinic, the plastic, reconstructive, and esthetic treatment methods applied to them after the two biggest earthquakes in Kahramanmaraş, Turkey. Materials and Methods: This is a descriptive cross-sectional study and was conducted with 38 earthquake victims who were treated at the plastic, reconstructive, and esthetic surgery unit of a medical school health and research hospital in the Southeast Anatolia region of Turkey. Patient data were obtained retrospectively from electronic medical records, and descriptive statistical methods, Chi-square test, and post hoc were used for data analysis. Results: Of the earthquake victims, 55% were between 18 and 35 years old, 68% were female, 63% underwent plastic, reconstructive, and esthetic surgery due to upper extremity injuries, 50% had skin grafting, and 15% had amputation. In addition, 18.4% of the earthquake victims underwent surgery 3 times, and 13% were operated on 7 times. Conclusion: Careful attention should be paid to the treatment of upper extremity injuries that occur during major earthquakes. Delayed or inadequate interventions can result in amputation, highlighting the importance of plastic, reconstructive, and esthetic surgeons in disaster response teams. If possible, conservative treatment should be preferred for fractures in disaster environments. Amputation should always be the last treatment option for crush injuries. In cases requiring surgery, time should not be wasted.